2016
DOI: 10.1111/ajco.12656
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing combination dabrafenib and trametinib therapy in BRAF mutation‐positive advanced melanoma patients: Guidelines from Australian melanoma medical oncologists

Abstract: BRAF mutations occur commonly in metastatic melanomas and inhibition of mutant BRAF and the downstream kinase MEK results in rapid tumor regression and prolonged survival in patients. Combined therapy with BRAF and MEK inhibition improves response rate, progression free survival and overall survival compared with single agent BRAF inhibition, and reduces the skin toxicity that is seen with BRAF inhibitor monotherapy. However, this combination is associated with an increase in other toxicities, particularly dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
1
24
0
1
Order By: Relevance
“…To avoid hypovolaemia with hypotension and possible acute renal failure, sufficient fluid substitution is important. As soon as the fever ceased for at least 24 hours, BRAFi+MEKi therapy can be restarted 48. Patients experience a median of two events of fever, with 21% of patients having > 4 events 47.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid hypovolaemia with hypotension and possible acute renal failure, sufficient fluid substitution is important. As soon as the fever ceased for at least 24 hours, BRAFi+MEKi therapy can be restarted 48. Patients experience a median of two events of fever, with 21% of patients having > 4 events 47.…”
Section: Methodsmentioning
confidence: 99%
“…A dose reduction is recommended if fever recurs. However, clinical experience shows that short ‘drug holidays’ (about 2–7 days) are much more effective and the full dose can be maintained 48. In recurrent cases, intermittent treatment might be an option to avoid additional fever events.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the clinical blood markers that reflect the course of pyrexia during combi‐DT may be helpful for the appropriate management and may result in a shortened drug holiday. For pyrexia management, temporary withdrawal or the dose reduction of combi‐DT and the administration of anti‐inflammatory agents, including corticosteroids, has been recommended . However, some reports have indicated that the dose reduction of the combi‐DT may be ineffective for the prevention of pyrexia and may confer clinical benefits .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Pyrexia during combi-DT is known to be refractory and is characterized by accompanying chills and influenza-like reactions; 4,5 therefore, the clinical management of the condition is important for the continuation of combi-DT. Although previous reports have suggested management strategies for pyrexia, [3][4][5][6][7][8] no appropriate procedure has been established. Moreover, accurate evaluation of the condition of pyrexia during combi-DT allows appropriate management, but blood markers that reflect the course of pyrexia have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, combination therapy leads to higher toxicity compared to a single agent [12] . Anti PD-1 inhibitors (Nivolumab and Pembrolizumab) are also used in melanoma.…”
Section: Newer Tumor Markersmentioning
confidence: 99%